Spectral properties of silver and gold nanoshells with silica core in biotissues - Trusevich, Liubou A.; Kugeiko, Mikhail M. (Journal of the Belarusian State University. Physics, 2026)
Using the MiePlot software package, the spectral properties of plasmon resonance in silver and gold nanoshells with silica core used in biotissues (cells of skin, adrenal glands, mammary glands) as contrast agents for optical visualization (fluorescence microscopy, spatially resolved spectroscopy, etc.) and therapy of pathological foci were modelled. It was determined that the most effective action is provided either by silver nanoshells with thickness of 5 nm at resonance wavelength from 845 to 855 nm, or gold nanoshells with thickness of 10 nm at resonance wavelength from 758 to 764 nm. However, resonance frequencies of silver nanoshells with thickness of 10 nm and gold nanoshells with thickness of 5 nm, whose spectra are located at the edges of transparency window of biotissues, can also be used for diagnostic purposes, enabling the selection of nanoshell sizes introduced into the human body and the choice of laser radiation sources for optical visualisation. The possibilities of tunability of plasmon resonance properties in silver and gold nanoshells by altering their size, composition and environment are demonstrated. The obtained results can be applied to the creation of nanostructures designed for specific therapeutic purposes, visualisation of pathological foci and monitoring them during treatment. It has been established that, with a normal distribution of particles, the scattering cross-sections of light by monodisperse nanoshells and the resonance wavelengths of these nanoshells differ only slightly from the scattering cross-sections of light by polydisperse particles and the resonance wavelengths of such nanoshells (by hundredths for scattering cross-sections of light and by no more than 2 nm for wavelengths). It is concluded that the practical use of polydisperse silver and gold nanoshells with silica core is advisable due to the requirement reduction for the nanoshell size dispersion.
Keywords: silver and gold nanoshells with silica core; spectral properties of nanoshells; mono- and polydisperse nanoshells; biotissues (cells of skin, adrenal glands, mammary gland); theranostics